Examining Children's Interests in Divorce Conflict Resolution from an Islamic Family Law Perspective - Iin Rahayu (Journal of Nafaqah, 2024)
This research discusses the importance of taking into account the interests of children in the context of divorce from the perspective of Islamic family law. In divorce, children are often the vulnerable parties and are often direct witnesses to their parents' conflict, which can adversely affect their well-being physically, emotionally and psychologically. Although Islamic family law provides clear guidelines on children's rights, its implementation in practice is often complex and influenced by cultural, social and economic factors. This article explores how children's interests can be preserved and prioritized in the resolution of divorce conflicts according to Islamic family law, as well as the challenges and obstacles faced in implementing these principles. The research methods used include literature review, case studies, interviews and document analysis. The results of this research are expected to provide a more comprehensive understanding of how children's interests are championed in divorce from an Islamic family law perspective, as well as provide a stronger foundation for the development of legal policies and practices that favor the protection and welfare of children. To fulfill the objectives of this research, a qualitative method was used involving in-depth analysis of Islamic legal literature, case studies, interviews, and document analysis. The results of this research include an in-depth understanding of children's interests, analysis of legal practices, identification of challenges and barriers, recommendations for policy and practical action, contribution to academic literature, raising public awareness, developing a model approach based on child welfare, and influence on public policy. In conclusion, this research makes a significant contribution to understanding and protecting children's interests in divorce from an Islamic family law perspective, and provides direction for policies and practices that are more responsive to the protection and welfare of children.